Tourists’ Health Risk Threats Amid COVID-19 Era: Role of Technology Innovation, Transformation, and Recovery Implications for Sustainable Tourism - Li, Zhenhuan; Wang, Dake; Abbas, Jaffar; Hassan, Saad; Mubeen, Riaqa (Frontiers in Psychology, 2022)
Technology innovation has changed the patterns with its advanced features for travel and tourism industry during the outbreak of COVID-19 pandemic, which massively hit tourism and travel worldwide. The profound adverse effects of the coronavirus disease resulted in a steep decline in the demand for travel and tourism activities worldwide. This study focused on the literature based on travel and tourism in the wake global crisis due to infectious virus. The study aims to review the emerging literature critically to help researchers better understand the situation. It valorizes transformational affordance and tourism and travel industries impacts posed by the virus COVID-19. The study proposed a research model on reviving the international tourism activities post COVID-19 pandemic to gain sustainable development and recovery. The scholars have debated seeking the best possible ways to predict a sustainable recovery of travel, tourism, and leisure sectors from the devastating consequences of coronavirus COVID-19. In the first phase, the study describes how the current pandemic can become transformational opportunities. It debates the situation and questions related to the emergence of the COVID-19 outbreak. The present research focuses on identifying fundamental values, organizations, and pre-assumptions related to travel and tourism revival and help academia and researchers to a breakthrough in initiating the frontiers based on research and practice. This study aims at exploring the role of technological innovation in the crisis management of COVID-19 tourism impacts, tourists' behavior, and experiences. The travel and tourism industry's main stakeholders include tourism demand and organizations that manage tourists' destinations and policymakers. They have already experienced the stages of responses, recovery, and resetting tourism recovery strategies. The study provides valuable insight into the coronavirus consequences on travel and tourism and practical implications for global tourism and academic research revitalization.